Menciptakan Calon Perwira Kapal Penangkap Ikan Bertaraf Internasional Melalui Sertifikasi Profesi Calon Pelaut yang Handal dan Berdedikasi Tinggi serta Berbudaya Indonesia Untuk Alumni Taruna SMK Kemaritiman - Helmi Ibrahim (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2018)
This article aims to mobilize and unite the steps of stakeholders to create prospective fishing vessels, especially maritime vocational cadets where the existence of SMKN 4 Pangkalpinang, SMKN2 Sungailiat, and SMKN1 Tukak Sadai under the auspices of the Provincial Bangka Belitung Islands Education Office and Maritime Affairs and Fishery. This research is a correlative descriptive study so that the data is analyzed to determine the relationship between Vocational High Schools maritime cadets and the Government of the Bangka Belitung Islands which is very closely related to the success of vocational education to produce potential fishing vessel officers. The instrument for data collection uses documentation, questionnaires, and direct observations which are then analyzed using simple linear correlation. The results obtained were government policies in providing overall support in developing Maritime Vocational High Schools in the Bangka Belitung Islands Province including laboratory facilities (SMKN 4 Pangkalpinang: 80%, SMKN2 Sungailiat : 45%, SMKN1 Tukak Sadai : 45%), Infrastructure practice tools (SMKN 4 Pangkalpinang: 75%, SMKN 2 Sungailiat: 50%, SMKN1 Tukak Sadai : 30%), Simulator (SMKN 4 Pangkalpinang: 50%, SMKN2 Sungailiat : 100%, SMKN1 Tukak Sadai : 0%) , Ships (SMK 4 Pangkalpinang: 100%, SMKN2 Sungailiat : 100%, SMKN1 Tukak Sadai : 50%).